Strategi Pemasaran Museum Gunung Api Batur sebagai Daya Tarik Wisata Edukasi di Kabupaten Bangli - Dwiyanti, Ni Made Christine; Luh Putu Agustini Karta, Ni; Cintya, Ni Putu; Bendesa, I Nyoman Gede Prananta (Penerbit Goodwood, 2023)
Purpose: This research aims to analyze the marketing strategy for the Batur Volcano Museum as an educational tourism attraction. Research Methodology: This was descriptive qualitative research with seven key informants. The research analysis technique uses SWOT analysis. Results: This study were that the position of the Batur Volcano Museum is in quadrant I (one), namely in the growth phase, with an IFAS (Internal Factor Analysis Score) of 3.13 and an EFAS (External Factor Analysis Score) of 2.98. The appropriate strategies implemented in this study are market development, market penetration, and product development. Activities suggested are offline and online promotions through social media, collaboration with schools for the tourism programs at museums, cooperation with travel agents, and information updates through digital marketing. Limitations: of this research is that it focuses on SWOT analysis techniques on marketing strategies, which need another approach to explore using another kind of analysis. Contribution: The contribution of this research was supporting the sustainability of the destination, especially for education tourism.